PREGNANT MARRIAGE MASLAHAH PERSPECTIVE - Tarmizi, Tarmizi; Hamzah, Ekawati (Journal of Islam and Science, 2022)
This paper discusses "Pregnant Marriage according to Religious Court Judges from the Maslahah Perspective" by revealing the problems, namely: (1) How is the implementation of Article 53 KHI regarding pregnant marriage, (2) What are the implications of implementing Article 53 KHI regarding pregnant marriage? And (3) How is the analysis of the judges of the religious courts on Article 53 of the KHI concerning marriage and pregnancy from a maslahah perspective? The Religious Courts do not directly handle cases of pregnant women, while cases that are related to pregnant women are cases of marriage isbat and marriage dispensation. The marriage of a pregnant woman affects the status of the child that the woman is carrying. By holding a marriage for pregnant women and men who impregnate them, they will maintain the lineage of children, inheritance and guardianship of the children they contain. Article 53 Compilation of Islamic Law regarding pregnant marriage contains many benefits for society in general, especially for pregnant women and the children they are carrying.